(8+w)(5w+7)=0

Simple and best practice solution for (8+w)(5w+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8+w)(5w+7)=0 equation:


Simplifying
(8 + w)(5w + 7) = 0

Reorder the terms:
(8 + w)(7 + 5w) = 0

Multiply (8 + w) * (7 + 5w)
(8(7 + 5w) + w(7 + 5w)) = 0
((7 * 8 + 5w * 8) + w(7 + 5w)) = 0
((56 + 40w) + w(7 + 5w)) = 0
(56 + 40w + (7 * w + 5w * w)) = 0
(56 + 40w + (7w + 5w2)) = 0

Combine like terms: 40w + 7w = 47w
(56 + 47w + 5w2) = 0

Solving
56 + 47w + 5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(8 + w)(7 + 5w) = 0

Subproblem 1

Set the factor '(8 + w)' equal to zero and attempt to solve: Simplifying 8 + w = 0 Solving 8 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + w = 0 + -8 w = 0 + -8 Combine like terms: 0 + -8 = -8 w = -8 Simplifying w = -8

Subproblem 2

Set the factor '(7 + 5w)' equal to zero and attempt to solve: Simplifying 7 + 5w = 0 Solving 7 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 5w = 0 + -7 5w = 0 + -7 Combine like terms: 0 + -7 = -7 5w = -7 Divide each side by '5'. w = -1.4 Simplifying w = -1.4

Solution

w = {-8, -1.4}

See similar equations:

| 8-2x+2=5x+3 | | 8-2x+2=5x | | -4(n-3)= | | 7(x+35)=273 | | 13/15+(8/15)= | | 8.28=5r | | -2(6+x)= | | 2(x+12)=3*x-31 | | (10j-7)-(9j+2)= | | 3x+22+5y+11=180 | | 5y+11=180 | | x-2+3=7 | | (63+5)+(72-3)= | | 8+5(x+3)+7x=x | | (7y+1)(3y-4v-2)= | | 2(4x+1)=42 | | 9+3m= | | (7t+5)+(8t-3)= | | 4x^3-3x^2+9=0 | | 4x-8=79+9x | | 2x+2u=5 | | 1/2(6x-10)+1/3(6+9x)= | | 4x^2-19x+23=-4x+9 | | 12v-11v=18 | | 10(2.1q-2)+(7.5q+19)= | | 5x-2x-2x=17 | | 9m+m+3m-12m+3m=12 | | 8g-6g-8=2g | | 12z-11z=8 | | 5x+(3x-2)=-3-(-4x) | | x=(x*0.1)+(x*0.02)+5+100 | | (13x+50)-(80x+120)= |

Equations solver categories